Djunta Mon por uma rede transnacional feminista de combate à violência de gênero - Brasil/Cabo Verde: uma etnografia do projeto "Fla Sim pa Mudjer" - Reis, Janaína Perez (Universidade do Vale do Rio dos Sinos, 2024)
This thesis presents an analyzes of the construction of a common agenda around the prevention of gender-based violence within the framework of the project “Fla Sim pa Mudjer: women united preventing gender-based violence in Cape Verde”, developed by two organizations from the Global South: Themis Gênero, Justiça e Direitos Humanos (Brazil) and Associação Cabo-Verdiana de Luta contra a Violência Baseada no Gênero (Cape Verde). This project is under development and aims to “adapt” the experience of legal empowerment carried out by the Brazilian organization in Cape Verde, with funding received through an international award for South-South gender equity initiatives by Womanity (Switzerland). The legal training aimed at women community leaders, with a focus on confronting and ending gender violence from a feminist perspective, was called the Popular Legal Promoters Program (PLPs) in Brazil. The transnational partnership faces challenges in translating feminist theories, legislation and practices. In this research, the analysis will focus on some dimensions, especially the interactions and negotiations between the teams involved, i.e. the approaches to the methodologies involved in the project, as well as the circulation of the grammars employed aimed at gender equality and the agendas that emerged from this process. The ethnographic research took place from August 2022 to October 2023, involving field research in Cape Verde, a recorded interview with the president of ACLCVBG, documentary analysis of women's rights and GBV in Cape Verde, as well as institutional documents from both organizations and online interactions, and covered the period of organization of the first class, which in Cape Verde was called the training course for Women Citizenship Multipliers. Guided by a knowledge policy based on a situated perspective and anti-colonialist and anti-racist approaches to feminist practices, it was identified that the project laid the foundations for a transnational feminism in Praia/Cape Verde.
Keywords: Feminismos transnacionais; Violência de gênero; Sul global; Cabo Verde; Empoderamento legal; Transnational feminisms; Gender violence; Global south; Cape Verde; Legal empowerment; ACCNPQ::Ciências Humanas::Sociologia